2010
DOI: 10.1007/s10763-010-9254-z
|View full text |Cite
|
Sign up to set email alerts
|

Indian Secondary Students’ Views About Global Warming: Beliefs About the Usefulness of Actions and Willingness to Act

Abstract: A 44-item survey instrument was designed to determine secondary students' views about how useful various specific actions related to reducing global warming might be, their willingness to undertake these various actions and the extent to which these 2 might be linked. The instrument was administered to students in grades 6 -10 (n = 768) from 4 large schools in metropolitan Delhi, India in which the teaching language was English. The findings indicated that this cohort of Indian students exhibited high levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…After the experience, the students interviewed seemed to understand that their consumer habits affect society and the environment, but they are not prepared to change their ways, showing again the "breach" that can exist between cognition and action, as noted by various authors [59,60]. Studies, such as that by Álvarez, Sureda, and Coma (2018) [17] carried out in a similar Spanish context, also point to the poor commitment to action in solving socio-environmental problems by future teachers who have a high level of environmental awareness.…”
Section: Speaking About Our Socioeconomic Model and Our Responsibilitmentioning
confidence: 98%
“…After the experience, the students interviewed seemed to understand that their consumer habits affect society and the environment, but they are not prepared to change their ways, showing again the "breach" that can exist between cognition and action, as noted by various authors [59,60]. Studies, such as that by Álvarez, Sureda, and Coma (2018) [17] carried out in a similar Spanish context, also point to the poor commitment to action in solving socio-environmental problems by future teachers who have a high level of environmental awareness.…”
Section: Speaking About Our Socioeconomic Model and Our Responsibilitmentioning
confidence: 98%
“…Table 8 shows the categories generated from the analysis of the answers regarding the actions proposed by students to mitigate climate change. With the exception of the categories labelled as reducing production in factories, not throwing rubbish into rivers and seas, and reduce CGC emissions, all the others were taken or adapted in interaction with data from previous studies (Boyes et al 2009;Chhokar et al 2011;Authors 2012;Papadimitriou 2004). From the results obtained in this study, it is noted that a large proportion of students in the pre-test and post-test suggested a reduction of vehicle use and proposed increasing the use of public transport and cycling or walking short distances (45%).…”
Section: Tablementioning
confidence: 99%
“…; and external factors such as institutional, economic, social, and cultural factors. The second type of research, represented by numerous works, tested the impact of one or more specific variables on a well-defined pro-environmental behavior and in a particular context, using qualitative and quasiexperimental methods (Bonaiuto, Carrus, Martorella & Bonnes, 2002;Chhokar, Dua, Taylor, Boyes & Stanisstreet, 2011;Cialdini, Reno & Kallgren, 1990;Corraliza & Berenguer, 2000;Hadjichambis, Paraskeva-Hadjichambi, Ioannou, In general, we can say that the variables influencing the pro-environmental behavior, stated by all the researchers above, can be classified according to their degree of influence, direct or indirect, in two main categories, some of which lead to the others. That is, some variables are less correlated with behaviors and enter into the training or education phase.…”
Section: Introductionmentioning
confidence: 99%